k
+ div(
k
v
k
) = 0 (1.1)
t
v
k
+
k
v
k
.v
k
= p (1.2)
where k is the gas G or the liquid L depending on whether one considers the gas or liquid and p the
state equation of the gas.
Let Y
L1
, Y
L2
(resp. Y
G1
, Y
G2
) the mass fractions of the liquid (resp. gas) obtained after diusion of
species in the surrounding gas. Therefore for two species, one has
Y
G1
+Y
G2
= Y
L1
+Y
L2
= 1.
Along with equation (1.1), we have to add the equation giving the conservation of species. So for
the liquid we have
t
Y
Lk
+
L
v
L
.Y
Lk
+ div(
L
Y
Lk
v
Lk
) =
L
f(Y
Lk
), k = 1, 2 (1.3)
Y
Lk
denoting the mass fraction of the liquid, and f a continuous function associated to a friction or
a resistance for the drop.
We assume that the speed of the liquid is small, and thus settled it to 0. Equations (1.1) and (1.3)
can then be written under conservative form as
t
( g) + div( gv) = F( g) (1.4)
or
t
u +
x
(f(u)) = F(u) (1.5)
3
in a system of particular coordinates.
If is a curve of discontinuity of u, then one has
[f(u)] = [u]
dx
dt
(1.6)
where [.] denotes the jump of the inner quantity, s =
dx
dt
is the speed of discontinuity along . The
jump Relation (1.6) is known as RankineHugoniot condition. It merely means that discontinuities
cannot be completely arbitrary. These classical facts are detailed for instance in [4].
In the case of the drop, to nd interface condition at the surface of the drop i.e. for r = R(t), it is
sucient to use (1.5) and (1.4) in polar coordinates, getting
[ gv] = [ g]
dR
dt
. (1.7)
Thus taking g = 1, one has
(
G
L
)
dR
dt
=
G
v
G
L
v
L
that is also with v = 0
G
_
v
G
dR
dt
_
=
L
dR
dt
. (1.8)
Taking g = Y in (1.7), Y denoting the mass fraction of the liquid or the gas after diusing, we get
(
G
Y
Gk
L
Y
Lk
)
dR
dt
=
G
Y
Gk
(v
G
+v
Gk
)
L
Y
Lk
v
Lk
and this is equivalent to
G
Y
Gk
(v
G
R
) +
G
Y
Gk
v
Gk
=
L
Y
Lk
R
+
L
Y
Lk
v
Lk
. (1.9)
Above v
Gk
(resp.v
Lk
) is the speed of the specie Gk (resp.Lk), k = 1, 2.
Combining relation (1.9) with Ficks law, see [3,4], that is
Y
G1
v
G1
=
D
12
Y
G1
, Y
G2
v
G2
= D
21
G
G2
where D
12
and D
21
are diusion coecients, and with equations relating the thermodynamic state
at the interface r = R(t)
Y
Gk
= K
k
Y
Lk
, k = 1, 2
we obtain for the mass fraction of the liquid Y
L1
the boundary condition
4
r
Y
L1
+
R
(t)(K
1
1)
K
2
G
(R(t), t) K
3
Y
L1
= 0, at r = R(t) (1.10)
using polar coordinates.
In [2] we have made huge mathematical and physical simplications taking the state equation of the
gas p as constant in (1.2) and considering the velocity of the gas v
G
as a given function of the time
t. Thus in our previous work, the system (1.1), (1.2) was reduced to the equation (1.1) with v
G
(t)
given.
In this paper, we rst analyze the hyperbolic system (1.1), (1.2) with an auxiliary state equation
of the gas p
1
=
. Once
G
(r, t) and v
G
(r, t) determined, we compute the radius R(t) of the drop
suspended in the gas through the ordinary dierential equation (1.8). R(t) being known, we shall
then study the mass fraction Y
L1
of the liquid after the evaporation process through the PDE (1.3)
along with the boundary condition (1.10), with a function f submitted to suitable assumptions.
Let us note that spherical symmetry reduces the problem to a transcent process of 1dimensional
nature. Within the framework of weighted Sobolev spaces on initial data and for some continuous
function f subject to increasing condition, we shall provide an unique local solution for the mass
fraction Y
L1
of the liquid. In addition, we shall show that if the initial condition is bounded, then
so is our solution.
2. HYPERBOLIC SYSTEM
The velocity v
G
(r, t) of the gas and its density
G
(r, t) satisfy the following system, using polar
coordinates
G
t
+
1
r
2
r
_
r
2
G
v
G
_
= 0
t
(
G
v
G
) +
1
r
2
r
_
r
2
G
v
2
G
_
=
p
r
(2.1)
Setting (r, t) = r
2
G
(r, t), v(r, t) = v
G
(r, t) we have
t
+v
r
+
v
r
= 0
v
t
+v
v
r
=
1
p
1
r
(2.2)
where p
1
(r, t) is an auxiliary function connected to the state equation of the gas p(r, t) by
p
1
r
=
r
2
p
r
.
In (2.2) we choose the auxiliary function p
1
(r, t) such that p
1
=
, > 1.
In this way, we have to consider the following system
t
+v
r
+
v
r
= 0
v
t
+v
v
r
+
2
p
r
= 0
(2.3)
5
(2.3) is equivalent to
t
_
v
_
+A.
r
_
v
_
= 0, (2.4)
A being the matrix (2, 2)
A =
_
v
2
v
_
The eigenvalues of A (characteristics speeds) are = v c and = v + c, c =
_
1
. Since
< , system (2.4) is hyperbolic. Then there exists two functions W(, v) and Z(, v) (Riemann
invariants) such that
W(, v) = constant on
dX
1
dt
= (2.5)
Z(, v) = constant on
dX
2
dt
= . (2.6)
W(, v) is determined by the system
dv
c/
=
d
1
, the vector R
1
= (1, c/) being the eigenvector
associated to the eigenvalue . Thus
W(, v) = v
2c
1
(2.7)
In the same way, the Riemann invariant Z(, v) corresponding to is given by
Z(, v) = v +
2c
1
(2.8)
The functions W(, v) = W(t, r) and Z(, v) = Z(t, r) satisfy the following system equivalent to
system (2.4)
W
t
+(W, Z)
W
r
= 0
Z
t
+(W, Z)
Z
r
= 0
(2.9)
where (W, Z) and (W, Z) are given by
=
_
3
4
_
Z +
_
+1
4
_
W
=
_
+1
4
_
Z
_
3
4
_
W
(2.10)
as can be seen from (2.7) and (2.8).
It is well known that a sucient condition in order that (2.9) is authentically nonlinear is that
W
> 0 and
Z
> 0, which is the case here according to (2.10).
6
Integration along the characteristics dened by
dX
1
dt
= (W, Z), X
1
(0) =
gives
X
1
(0,)
(t) = +
_
t
0
(W(s, X
1
(s)), Z(s, X
1
(s)))ds (2.11)
and therefore the solution of the value initial problem
W
t
+(W, Z)W
r
= 0, W(0, r) = W
0
(r) (2.12)
can be written as
W(t, r) = W
0
_
X
1
(0,)
(0)
_
= W
0
(), (2.13)
where = r
_
t
0
(W(s, X
1
(s)), Z(s, X
1
(s)))ds.
Similarly we have
Z(t, r) = Z
0
_
X
2
(0,)
(0)
_
= Z
0
() (2.14)
where
X
2
(0,)
(t) = +
_
t
0
(W(s, X
2
(s)), Z(s, X
2
(s)))ds.
Proposition 2.1. Let us suppose that W
0
() < 0 or Z
0
() < 0. Then the solution of system (2.3)
is dened on a nite interval [0, T[.
Proof
Dierentiation of (2.5) and (2.11) with respect to gives
dX
1
dt
=
(W, Z) with X
1
(t = 0) = 1. (2.15)
In the same way
dX
2
dt
=
(W, Z) with X
2
(t = 0) = 1. (2.16)
But
=
W
W
+
Z
Z
=
W
W
0
() and
=
Z
Z
0
(). Using these results in (2.15) and (2.16)
and integrating w.r.t. t along the characteristics gives
7
X
1
(t) = 1 +
_
t
0
W
W
0
()dt = 1 +
_
+ 1
4
_
W
0
()t (2.17)
X
2
(t) = 1 +
_
t
0
Z
Z
0
()dt = 1 +
_
+ 1
4
_
Z
0
()t (2.18)
From (2.17) we see that X
1
(t
1
) = 0 for t
1
=
4
( + 1)W
0
()
> 0. Similarly X
2
(t
2
) = 0 for t
2
=
4
( + 1)Z
0
()
> 0. Hence
W
r
(t, r) becomes innite for T = inf {t
1
, t
2
} since
W
r
= W
.
d
dX
=
W
0
()
X
G
(t, R(t))
L
, R(0) = R
0
. (2.19)
The Cauchy problem (2.19) has an unique solution R(t) on a maximal time interval [0, T
[ with
T
0
(r) < 0 or Z
0
(r) < 0.
3. MASS FRACTION OF THE LIQUID
The mass fraction of the liquid Y
L1
satises the conservation equation of specie (1.3) which can be
rewritten as
t
Y
L1
1
r
2
r
_
r
2
r
Y
L1
_
+f(Y
L1
) = 0 (3.1)
using polar coordinates, the diusion constant D
12
being taken equal to 1. Then (3.1) is equivalent
to
t
Y
L1
Y
L1
2
r
r
Y
L1
+f(Y
L1
) = 0
,
for 0 < r < s(t) (3.2)
where s(t) = R(t) is the radius of the drop determined in section II.
The boundary condition at the surface s(t) is given by the RankineHugoniot condition connected
to the thermodynamic equilibrium i.e. formula (1.10). With the change of variable r = R(t)x, the
function Y
L1
(t, r) becomes the function Y
L1
(t, R(t)x) = u(t, x) which satises the following initial
boundary value (i.b.v.) problem
8
t
u a(t)
_
u +
2
x
x
u
_
x
R
(t)
R(t)
x
u +f(u) = 0, 0 < x < 1, t > 0 (3.3)
lim
x0+
xu
x
(t, x) < , u
x
(t, 1) +k(t)u(t, 1) = 0 (3.4)
u(0, x) = u
0
(x) (3.5)
where
a(t) =
1
R
2
(t)
, k(t) =
R(t)R
(t)(K
1
1)
K
2
G
(t, R(t)) K
3
. (3.6)
Denote by =]0, 1[ and H for the Hilbert space dened by
H = {v : R, measurable and such that
_
1
0
x
2
v
2
(x)dx < +}.
Note that H is the closure of C
0
(
H
_
. In the following, we shall often use the fact that V
is the closure of C
1
(
2
H
_
1/2
. V is continuously embedded in
H. Identifying H with his dual H
, one has V H V
, v
>.
We then have the following results, the proofs of which can be found in [6].
Lemma 3.1. For every v C
1
([0, 1]), > 0 and x [0, 1] we have
v
2
0
=
1
2
v
2
0
+v
2
(1)
v
2
(1) v
2
0
+C
v
2
0
v(x)
2 v
1
,
xv(x)
5v
1
where C
= 3 +
1
and .
0
= .
H
, .
1
= .
V
.
2
0
+v
2
(1)
_
1/2
and v
1
are two equivalent norms on V
since
9
2
3
v
2
1
v
2
(1) +v
2
0
5v
2
1
, v V.
(0,T;X)
= ess sup
0<t<T
u(t)
X
, for p = .
Let u(t), u
(t), u
x
(t), u
xx
(t) denote u(t, x),
u
t
(t, x),
u
x
(t, x),
2
u
x
2
(t, x) respectively.
We shall make the following assumptions:
(H
1
) u
0
H
(H
2
) a, k W
1,
(0, T), a(t) a
0
> 0
(F
1
) f C(R, R)
(F
2
) There exists positive constants C
1
, C
1
, C
2
and p, 1 < p < 3 such that
(i) uf(u) C
1
u
p
C
1
(ii) f(u) C
2
(1 +u
p1
)
Let u C
2
([0, T] [0, 1]) be a solution of problem (3.3)(3.5). Then, after multiplying equation (3.3)
by x
2
v, v V w.r.t. the scalar product of the space H, integrating by parts and taking into account
boundary condition (3.4), we get
d
dt
< u(t), v > + a(t)
_
1
0
x
2
u
x
v
x
dx +a(t)k(t)u(1)v(1)
R
(t)
R(t)
_
1
0
x
3
u
x
vdx+ < f(u), v >= 0
The weak formulation of the ibv problem (3.3)(3.6) can be given in the following way:
10
Find u(t) dened in the open set (0, T) such that u(t) satises the following variational problem
d
dt
< u(t), v > + a(t; u(t), v)+ < f(u(t)), v >= 0, v V (3.7)
and the initial condition
u(0) = u
0
(3.8)
where
a(t; u, v) = a(t)
_
1
0
x
2
u
x
v
x
dx +a(t)k(t)u(1)v(1)
R
(t)
R(t)
_
1
0
x
3
u
x
vdx, u, v V . (3.9)
We then have the following lemma, the proof of which can be found in [2]
Lemma 3.3. There exists constants K
T
,
T
and
T
depending on T such that
 a(t; u, v) K
T
u
1
v
1
, for all u, v V, (3.10)
a(t; u, u)
T
u
2
1
T
u
2
0
, u, v V. (3.11)
(0, T; H), x
2/p
u L
p
(Q
T
)
tu L
(0, T; V ), tu
t
L
2
(0, T; H).
Furthermore, if f satises the additional condition
(f(u) f(v))(u v) u v
2
,
for all u, v R, for some R, then the solution is unique.
j=1
c
mj
(t)w
j
(3.12)
11
where c
mj
(t) satisfy the following system of nonlinear dierential equations
< u
m
(t), w
j
> + a(t; u
m
(t), w
j
)+ < f(u
m
(t)), w
j
>= 0, 1 j m (3.13)
and the initial condition
u
m
(0) = u
0m
(3.14)
where
u
0m
u
0
strongly in H. (3.15)
It is clear that for each m, there exists a solution u
m
(t) of the form (3.12), which satises (3.13) and
(3.14) almost everywhere on 0 t T
m
, for some T
m
, 0 < T
m
T. The following estimates allow
us to take T
m
= T for all m.
Step2. A priori estimates.
(a) the rst estimate:
Multiplying the j
th
equation of the system (3.13) by c
mj
(t) and summing up w.r.t. j, we have
1
2
d
dt
u
m
(t)
2
0
+ a(t; u
m
(t), u
m
(t))+ < f(u
m
(t)), u
m
(t) >= 0 (3.16)
Using assumption (H
2
), (F
2
,i), Lemma 3.1 and Remark 3.1, it follows from (3.16) that
d
dt
u
m
(t)
2
0
+ 2
T
u
m
(t)
2
1
+ 2C
1
_
1
0
x
2
u
m
(t, x)
p
dx
2C
1
3
+ 2
T
u
m
(t)
2
0
(3.17)
Integrating (3.17), with (3.15), we have
S
m
(t) C
0
+
2
3
TC
1
+ 2
T
_
t
0
S
m
(s)ds, (3.18)
where
S
m
(t) = u
m
(t)
2
0
+ 2
T
_
t
0
u
m
(s)
2
1
ds + 2C
1
_
t
0
ds
_
1
0
x
2
u
m
(s, x)
p
dx, (3.19)
and C
0
is a constant depending only on u
0
with u
0m
2
0
C
0
m.
By Gronwalls lemma, we obtain from (3.18)
S
m
(t)
_
C
0
+
2
3
TC
1
_
exp(2
T
t) M
T
, m, t, 0 t T
m
T, (3.20)
i.e. T
m
= T.
In the following M
T
will denote a generic constant depending only on T.
(b) the second estimate: replacing w
j
by t
2
u
m
in (3.8) gives
12
tu
m
)
2
0
+
1
2
d
dt
_
a(t)tu
m
2
0
+a(t)k(t)t
2
u
2
m
(1)
_
+
1
2
d
dt
_
t
2
_
1
0
x
2
f(u
m
)dx
_
= u
mx
2
0
d
dt
_
t
2
a(t)
+
1
2
u
2
m
(1)
d
dt
(t
2
a(t)k(t)) + 2t
_
1
0
x
2
f(u
m
)dx
+
R
(t)t
2
R(t)
_
1
0
x
3
u
mx
u
m
dx
(3.21)
where
f(z) =
_
z
0
f(y)dy. (3.22)
Integrating (3.21) w.r.t. time variable from 0 to t, we shall have, after some rearrangements
2
_
t
0
su
m
(s)
2
0
ds +a(t)tu
mx
(t)
2
0
+a(t)t
2
u
2
m
(t, 1)
= a(t)(1 k(t))t
2
u
2
m
(t, 1) +
_
t
0
_
s
2
a(s)
u
mx
(s)
2
0
ds
+
_
t
0
_
s
2
a(s)k(s)
u
2
m
(s, 1)ds + 2
_
t
0
R
(s)
R(s)
s
2
< xu
mx
(s), u
m
(s) > ds
+4
_
t
0
sds
_
1
0
x
2
f(u
m
(s, x))dx 2t
2
_
1
0
x
2
f(u
m
)dx.
(3.23)
By means of assumption (H
2
) and Remark 3.1, we get
a(t)tu
m
(t)
2
0
+a(t)t
2
u
2
m
(t, 1)
2
3
a
0
tu
m
(t)
2
1
t [0, T], m. (3.24)
Let us choose > 0 such that
a
1 k
<
a
0
3
(3.25)
where .
= .
L(0,T)
.
Using again Lemma 3.1, Remark 3.1 with > 0 as in (3.25) and rst estimate (3.20), we estimate
without diculty the terms in the r.h.s. of (3.23) as follows
a(t)(1 k(t))t
2
u
2
m
(t, 1) a
1 k
_
tu
m
(t)
2
1
+C
tu
m
(t)
2
0
_
a
0
3
tu
m
(t)
2
1
+M
T
(3.26)
_
t
0
_
s
2
a(s)
_
u
mx
(s)
2
0
ds +
_
t
0
_
s
2
a(s)k(s)
_
u
2
m
(s, 1)ds
__
_
(t
2
a)
_
_
+
_
_
(t
2
ak)
_
_
_
t
0
_
u
mx
(s)
2
0
+u
2
m
(s, 1)
_
ds
5
__
_
(t
2
a)
_
_
+
_
_
(t
2
ak)
_
_
_
t
0
u
m
(s)
2
1
ds M
T
(3.27)
13
2
_
t
0
s
2
R
(t)
R(t)
< xu
mx
(s), u
m
(s) > ds
_
t
0
su
m
(s)
2
0
ds +
_
_
_
_
R
R
_
_
_
_
2
_
t
0
su
m
(s)
2
1
ds. (3.28)
On the other hand, from assumptions (F
1
) and (F
2
), we have
m
0
=
_
z
0
z
0
f(y)dy
f(z) =
_
z
0
f(y)dy C
2
_
z +
z
p
p
_
, z R (3.29)
where z
0
= (C
1
/C
1
)
1/p
.
Using the rst estimate (3.20), (3.29) and Lemma 3.1, we obtain
4
_
t
0
sds
_
1
0
x
2
f(u
m
(s, x))dx 2t
2
_
1
0
x
2
f(u
m
(t, x)dx
4C
2
_
t
0
sds
_
1
0
x
2
_
u
m
(s, x) +
1
p
u
m
(s, x)
p
_
dx + 2t
2
_
1
0
x
2
m
0
dx
4C
2
_
t
0
su
m
(s)
0
ds +
4
p
C
2
t
_
t
0
ds
_
1
0
x
2
u
m
(s, x)
p
dx +
2
3
T
2
m
0
2C
2
T
_
M
T
+
2C
2
pC
1
TM
T
+
2
3
T
2
m
0
M
T
.
(3.30)
Hence, we deduce from (3.23),(3.24),(3.26)(3.28) and (3.30) that
_
t
0
su
m
(s)
2
0
ds +
a
0
3
tu
m
(t)
2
1
M
T
+
_
_
_
_
R
R
_
_
_
_
2
_
t
0
su
m
(s)
2
1
ds. (3.31)
By Gronwalls lemma, it follows that
_
t
0
su
m
(s)
2
0
ds +
a
0
3
tu
m
(t)
2
1
M
T
exp
_
_
_
_
_
R
R
_
_
_
_
2
.
3T
a
0
_
M
T
, t [0, T]. (3.32)
On the other hand, by using (3.20) and assumption (F
2
,ii) we have
_
t
0
ds
_
1
0
x
2/p
f(u
m
(s, x))
dx (2C
2
)
p
_
t
0
ds
_
1
0
x
2
u
m
(s, x)
p
dx M
T
(3.33)
with p
=
p
p 1
.
step3: The limiting process.
By (3.20), (3.32) and (3.33) we deduce that there exists a subsequence of {u
m
}, still denoted {u
m
}
such that
u
m
u weakly in L
(0, T; H)
u
m
u weakly in L
2
(0, T; V )
x
2/p
u
m
x
2/p
u weakly in L
p
(Q
T
)
tu
m
tu weakly in L
(0, T; V )
(tu
m
)
(tu)
weakly in L
2
(0, T; H).
(3.34)
14
A compactness lemma ([5] p.57) and formula (3.34) enables us to extract from the sequence {u
m
}
a subsequence still denoted by {u
m
} such that
tu
m
tu strongly in L
2
(0, T; H). (3.35)
The continuity of f implies
f(u
m
(t, x)) f(u(t, x)) a.e. (t, x) Q
T
= (0, T) (0, 1) (3.36)
since we have the convergence of u
m
(t, x) to u(t, x) a.e. (t, x) Q
T
.
Applying a weak convergence lemma (see [5]) we obtain
x
2/p
f(u
m
) x
2/p
f(u) weakly in L
p
(Q
T
).
Passing to the limit in (3.13), (3.14), then by (3.15), (3.34) and (3.36) one can show that the function
u(t) satises the i.b.v. problem (3.7), (3.8).
step4: Uniqueness of the solutions.
First of all, we shall need the following lemma, which is a slight improvement of a lemma used in
[2] (see also [5])
Lemma 3.4. Let w be the weak solution of the i.b.v. problem
w
t
a(t)(w
xx
+
2
x
w
x
) =
f(t, x), 0 < t < T, 0 < x < 1,
lim
x0+
xw
x
(t, x)
< +, w
x
(t, 1) +k(t)w(t, 1) = 0, w(0, x) = 0,
w L
2
(0, T; V ) L
(0, T; H), x
2/p
w L
p
(Q
T
)
tw L
(0, T; V ), tw
t
L
2
(0, T; H).
Then
1
2
w(t)
2
0
+
_
t
0
a(s)
_
w
x
(s)
2
0
+k(s)w
2
(s, 1)
_
ds
_
t
0
<
f(s), w(s) > ds = 0,
a.e. t (0, T)
Uniqueness of the solution will be deduced as follows. Let u and v be two weak solutions of
(3.3)(3.5). Then w = u v is a weak solution of the associated problem mentioned in Lemma
3.4, with the r.h.s. function
f(t, x) =
xR
(t)
R(t)
w
x
f(u) +f(v). Lemma 3.4 gives
1
2
w(t
2
0
+
_
t
0
a(s; w(s), w(s))ds + 2
_
t
0
< f(u(s)) f(v(s)), w(s) > ds = 0.
Using Lemma 3.3 and (F
3
) we obtain
w(t)
2
0
+ 2
T
_
t
0
w(s)
2
1
2( +
T
)
_
t
0
w(s)
2
0
ds. (3.37)
15
If +
T
0 we have w(t)
0
= 0 by applying Gronwalls lemma. In the case where +
T
< 0 the
result is clearly still true.
This ends the proof of Theorem 3.1.
For the boundedness of solutions, we shall make use of the following assumptions
(H
1
) u
0
L
(0, 1), u
0
(x) M, a.e. x (0, 1)
(H
2
) a, k W
1,
(0, T), a(t) a
0
> 0, k(t) k
0
> 0
(F
1
) uf(u) 0 u R such that u u
0
(Q
T
).
t
Z a(t)
_
Z +
2
x
x
Z
_
x
R
(t)
R(t)
x
Z +f(Z +M) = 0, 0 < x < 1, t (0, T) (3.38)
lim
x0+
xZ
x
(t, x) < , Z
x
(t, 1) +k(t)[Z(t, 1) +M] = 0 (3.39)
Z(0, x) = u
0
(x) M (3.40)
Multiplying equation (3.38) by x
2
v, for v V , integrating by parts w.r.t. variable x and taking into
account boundary condition (3.39), one has after some rearrangements
_
1
0
x
2
Z
t
vdx +a(t)
_
1
0
x
2
Z
x
v
x
dx +a(t)k(t)Z(t, 1)v(1)
R
(t)
R(t)
_
1
0
x
3
Z
x
vdx
+
_
1
0
x
2
f(Z +M)vdx = Ma(t)k(t)v(1), v V
(3.41)
v V hence for v = Z
+
=
1
2
_
Z +Z
_
since u
0
L
(t)
R(t)
_
1
0
x
3
Z
+
x
Z
+
dx +
_
1
0
x
2
f(Z
+
+M)Z
+
dx = Ma(t)k(t)Z
+
(t, 1) 0
since
_
1
0
x
2
Z
t
Z
+
dx =
_
1
0,Z>0
x
2
(Z
+
)
t
Z
+
dx =
1
2
d
dt
_
1
0
x
2
Z
+

2
dx.
On the other hand, by assumption (H
2
) and Remark 3.1, we obtain
a(t)
_
1
0
x
2
Z
+
x
2
dx +a(t)k(t)
Z
+
(t, 1)
C
0
_
_
Z
+
(t)
_
_
2
1
, (3.42)
where
C
0
=
2
3
a
0
min{1, k
0
}.
16
Using the monotonicity of f(u) +u and (F
1
) we have
_
1
0
x
2
f(Z
+
+M)Z
+
dx =
_
1
0
x
2
_
f(Z
+
+M) f(M)
Z
+
dx +
_
1
0
f(M)x
2
Z
+
dx
_
1
0
x
2
Z
+
2
dx +
_
1
0
f(M)x
2
Z
+
dx
_
_
Z
+
_
_
2
0
.
(3.43)
Hence it follows from (3.41)(3.43) with Cauchys inequality applied to the term
(t)
R(t)
_
1
0
x
3
Z
+
x
Z
+
dx
d
dt
_
_
Z
+
(t)
_
_
2
0
+
C
0
_
_
Z
+
(t)
_
_
2
1
_
1
C
0
_
_
_
_
R
R
_
_
_
_
2
+ 2
_
_
_
Z
+
(t)
_
_
2
0
. (3.44)
Integrating (3.44), we get
_
_
Z
+
(t)
_
_
2
0
_
_
Z
+
(0)
_
_
2
0
+
_
1
C
0
_
_
_
_
R
R
_
_
_
_
2
+ 2
_
_
t
0
_
_
Z
+
(s)
_
_
2
0
ds. (3.45)
Since Z
+
(0) =
_
u(0, x) M
_
+
=
_
u
0
(x) M
_
+
= 0, hence using Gronwalls lemma, we obtain
Z
+
(t)
0
= 0. Thus u(t, x) M a.e. (t, x) Q
T
.
The case u
0
(x) M can be dealt with, in the same manner as above by considering Z = u + M
and Z
=
1
2
_
Z Z
_
. Thus we get Z
G
(t, R(t))
L
, R(0) = 1 (4.2)
with
_
_
_
v
G
(t, r) =
1
2
(W(t, r) +Z(t, r))
G
(t, r) =
1
2
3r
2
(Z(t, r) W(t, r)).
(4.3)
In gure 1 below, we have drawn the curve t R(t) on the time interval [0, 1] with a step h = 0.05
and
L
= 0.9.
0 0.2 0.4 0.6 0.8 1 1.2 1.4
0.1
0.2
0.3
0.4
0.5
0.6
0.7
0.8
0.9
1
t
d
2
Fig. 1
For the second example we have chosen the experimental conditions made by the LCSR in the study
of single drop evaporation, the drop being suspended from a silicate tube. Drops are made up of n
heptane fuel (
L
= 683 kg/mm
3
)) in air at normalized atmospheric pressure and with an initial speed
v
G
(0, r) = C
1
= 35mm/s. The initial density
G
(0, r) of the gas is taken as C
2
=
348
T
0
, T
0
= 373K.
So The solution of (4.1) can be written as
W(t, r) = C
1
3C
2
2
, =
1 +
_
1 4(r C
1
t)
3C
2
t
2
3C
2
t
,
Z(t, r) = C
1
+
3C
2
2
, =
1 +
_
1 + 4(r C
1
t)
3C
2
t
2
3C
2
t
.
Figures 2 and 3 represent the velocity v
G
(t, r) and the pressure
G
(t, r) given by (4.3) for (t, r)
(0, 1) (0, 1).
18
0
0.2
0.4
0.6
0.8
1
0
0.2
0.4
0.6
0.8
1
150
100
50
0
50
t
r
Fig. 2
0
0.2
0.4
0.6
0.8
1
0
0.2
0.4
0.6
0.8
1
0
0.5
1
1.5
2
2.5
3
3.5
4
x 10
4
t
r
Fig. 3
The curve of the radius t R(t) for this case is drawn in gure 4.
0.1 0.2 0.3 0.4 0.5 0.6 0.7 0.8
0
0.2
0.4
0.6
0.8
1
1.2
1.4
t
d
2
Fig. 4
19
Fig. 5
Since W
0
() < 0 the maximal existence interval is nite (Proposition 2.1) as can be seen in our
graphic. Let us remark that looking on the experimental curves made by the LCSR (gure 5) at the
beginning, the function t R(t) is increasing around the vicinity of t = 0. This fact is conrmed
by our model which represents a good improvement of our previous model(see [1]) in which the
velocity v
G
(t) was a given function of t.
REFERENCES
[1] R.A.Adams: Sobolev Spaces. Academic Oress, NewYork, 1975.
[2] R. Alexandre, A. Pham Ngoc Dinh, A. Simon and Nguyen Thanh Long: A mathematical model for
the evaporation of a liquid fuel droplet inside an innite vessel. Nonlinear Analysis and Applications.
Dedicated to V.Lakshmikantham on his 80th. bithday. Vol.1 (2003), 117140, Kluwer Publishing
Company.
[3] H.I.Jia: I. High pressure droplet vaporization. II. Laminar natural convection heat transfer over
a sphere. New Brunswick University, NewJersey (1993).
[4] L.D.Landau and E.M.Lifshitz: Fluid mechanics. Course of theoretical physics. vol.6, Pergamon
press, 1987.
[5] J.L.Lions: Quelques methodes de resolution des probl`emes aux limites non lineaires. Dunod
GauthierVillars, Paris 1969.
20
[6] Nguyen Thanh Long, Bui Tien Dung, Tran Minh Thuyet, On a nonlinear boundary value problem
for a nonlinear ordinary dierential operator in weighted Sobolev spaces. Z. Anal. Anw. 19 (2000),
No 4, 10351046.
[7] A.Odeide: Simulation numerique de levaporation dune goutte de combustible liquide. Inuence
de la pression. Th`ese de lUniversite dOrleans, 1999.
[8] F.A.Williams: Combustion theory. Redwood Citry, 1985.